IMPLEMENTATION OF INTERAGENCY ELECTRONIC INTERACTION IN THE COURSE OF RENDERING PUBLIC SERVICES OF LICENSING IN THE SPHERE OF HEALTHCARE THROUGH THE EXAMPLE OF THE MINISTRY OF HEALTHCARE OF THE ALTAI KRAI - Колядо, Владимир Борисович; Лазарев, Виталий Сергеевич; Колядо, Елена Владимировна; Трибунский, Сергей Иванович (Medicine in Kuzbass, 2018)
Object of research (observation). Information obtained in the course of interagency electronic interaction when licensing in the health field.Purpose of research – to study the structure of the information obtained in the course of interagency electronic interaction by the Ministry of Healthcare of the Altai Krai for a three-year period (2014-2016).Research methods. Statistic, analytic.Basic results. The held analysis has shown that in 2016 the largest specific weight of information obtained in the course of interagency electronic interaction was constituted by the information from the Uniform State Register of Legal Entities (41.2 %).Field of their application. Organization of medical activity.Conclusions. For a three-year period (2014-2016), the general amount of information obtained in the course of interagency electronic interaction has increased more than three times, which reflects the general tendencies of reduction of administrative barriers and optimization of document turnover.
Keywords: interagency electronic interaction; medical activity; licensing